2018
DOI: 10.1112/blms.12218
|View full text |Cite
|
Sign up to set email alerts
|

Generalizations of Capparelli's identity

Abstract: Using jagged overpartitions, we give three generalizations of a weighted word version of Capparelli's identity due to Andrews, Alladi and Gordon, and present several corollaries.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
32
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(33 citation statements)
references
References 21 publications
1
32
0
Order By: Relevance
“…Lepowsky and Milne [17] also showed that the Rogers-Ramanujan identities arise in character formulas for the level 2 standard modules for A (2) 2 , which was later proven using Z-algebras by Capparelli [5]. Capparelli additionally used Z-algebras to construct the level 3 standard modules for A (2) 2 , which relied on the discovery of two conjectural partition identities (which were first proven by Andrews [2], and later by Capparelli [6]; an analytic sum-side for Capparelli's identities was recently given by [7]). These identities were a significant development in the theory of vertex operator algebras, as they were the first notable examples of sum-product identities that had not previously appeared, but were instead discovered using vertex-operator-theoretic techniques.…”
Section: Introduction and Statement Of Resultsmentioning
confidence: 99%
“…Lepowsky and Milne [17] also showed that the Rogers-Ramanujan identities arise in character formulas for the level 2 standard modules for A (2) 2 , which was later proven using Z-algebras by Capparelli [5]. Capparelli additionally used Z-algebras to construct the level 3 standard modules for A (2) 2 , which relied on the discovery of two conjectural partition identities (which were first proven by Andrews [2], and later by Capparelli [6]; an analytic sum-side for Capparelli's identities was recently given by [7]). These identities were a significant development in the theory of vertex operator algebras, as they were the first notable examples of sum-product identities that had not previously appeared, but were instead discovered using vertex-operator-theoretic techniques.…”
Section: Introduction and Statement Of Resultsmentioning
confidence: 99%
“…x i +j+k+2l q 3(i +j +k +2l )(i +j +k +2l −1) 2 +3i +2j+ 3j (j −1) 2 +4k+ 3k (k −1) 2 +3l q 3 ; q 3 i q 3 ; q 3 j q 3 ; q 3 k q 6 ; q 6 l , (7.3) which is exactly [DL,Equation (2.6)] with r → k, s → j, t → i, → l, q → q 3 , a → q −2 , b → q −4 . We may instead arrive at a different analytic sum-side by first simplifying the expression (7.1).…”
Section: Analytic Sum-sides For Capparelli's Identitiesmentioning
confidence: 90%
“…Then, we have s o 1 (π) t o 2 (π) u e 1 (π) v e 2 (π) q |π| , (3. 16) i.e., the polynomial S µ (s, t, u, v, q, q). Similarly we consider the following four further specializations, corresponding to taking s = v = 0, t = u = 0, t = v = 0 and s = u = 0 respectively, and get the following theorem, which is a bounded version of (3.5) ∼ (3.8), where the unspecified sums are over all quadruples (i, j, k, l) ∈ N 4 such that i+j +k+l = N. Theorem 3.13.…”
Section: Application To a Companion Of Capparelli's Identitiesmentioning
confidence: 99%
“…The proof of the other two formulae can be given similarly and thus omitted. + π = (20,17,16,11,10,9,6,5,4,2) π 1 = (12,11,10,9,8,7,6,5,4,2) π 2 = (8, 6, 6, 2, 2, 2) Figure 4. π = π 1 + π 2 π 1 = (12, 11, 10, 9, 8, 7, 6, 5, 4, 2) π 6,4 = (12, 10, 8, 7, 6, 5, 4, 3, 2, 1) π = (4, 4, 4, 4) + Figure 5.…”
Section: 2mentioning
confidence: 99%
See 1 more Smart Citation